The Tosontsengel Mongolia world record sea‐level pressure extreme: spatial analysis of elevation bias in adjustment‐to‐sea‐level pressures. (4th November 2014) - Purevjav, Gomboluudev; Balling, Robert C.; Cerveny, Randall S.; Allan, Rob; Compo, Gilbert P.; Jones, Philip; Peterson, Thomas C.; Brunet, Manola; Driouech, Fatima; Stella, José Luis; Svoma, Bohumil M.; Krahenbuhl, Daniel; et al.
ABSTRACT A World Meteorological Organization (WMO) committee evaluated the record sea‐level pressure (SLP) measurement of 1089.4 hPa on 30 December 2004 in Tosontsengel, Mongolia (1724.6 m). Although instrumentation and data collection procedures were properly followed according to the assessment of the committee, concern was raised regarding the reliability of SLP adjustment from such a high‐elevation station. This paper addresses this concern with a number of analyses that look at relationships between SLP extremes and corresponding station elevation and temperature. First, we selected data from stations extracted from the Integrated Surface Database (ISD‐Lite) of NOAA's National Climate Data Center. A spatial analysis indicates that elevation shows little to no association (R2 values essentially zero) to extreme SLP. However, a second analysis between extreme SLP and air temperature indicates that high regionalism exists in spatial correlations (local R2) between those two variables. This relationship to temperature is likely the result of differences in SLP adjustment formulae used around the world. Based on this analysis, on the need to differentiate the SLP values adjusted using extremely cold temperatures (and generally high elevation), and following past WMO SLP guidelines, the WMO Rapporteurs for Climate and Weather Extremes therefore have created two distinct SLP records: (a) highest adjusted SLP (below 750 m), currently 1083.3 hPa recorded on 31 December 1968 at Agata, Evenhiyskiy, Russia; and (b) highest adjusted SLP (above 750 m), currently 1089.4 hPa (by Russian method; 1089.1 hPa by WMO formula) on 30 December 2004 in Tosontsengel, Mongolia. Future WMO guidance regarding SLP adjustment may lead to re‐evaluation of this and other SLP records.